Evidenciação de informações nas páginas web de prefeituras municipais mato-grossenses: uma análise de aderência à Lei de responsabilidade fiscal e à Lei de acesso a informação - Silva, Antonio Leite da (Universidade do Vale do Rio dos Sinos, 2013)
In the present study we attempted to assess the level of compliance with the requirements on information disclosure required by the Fiscal Responsibility Act and the Access to Information Act, in municipalities of Mato Grosso. The adherence level of municipal public management was observed from compliance index prepared based on the precepts established in the LRF and LAI, totaling 32 indicators of information. In theoretical reference were approached governance concepts applied to the context of management and public transparency. The research is classified as applied, quantitative, descriptive and documental. The sample consists of 56 municipalities in the state of Mato Grosso, which have populations above 10,000 inhabitants and maintains portal for internet access. Data were collected on websites of municipalities that compose the sample, in the month of May 2013. It is highlighted that the municipalities were segregated by five large middle regions. The results indicate a low adherence in Mato Grosso municipalities surveyed, the precepts established in the LRF and LAI as transparency in management. Regarding accordance with the LRF requires the average compliance found was 29.69%, while the average rate of accordance with requiring the LAI was only 18.23%. With this level of accordance to the LRF and LAI we observed an overall compliance of 24.11%. The municipalities that reported more information from the middle Southwest of Mato Grosso, with an average General Index of 27.68%. The previous Budget Guidelines Law was the item of compliance inherent LRF most publicized, and is present in 38 websites of the municipalities surveyed. Permission for recording electronic reports was the item according to LAI evidenced by 47 sampled municipalities. It was also observed from tests of mean differences, that municipalities with higher GDP, higher RCL and higher annual budget, tend to disclose more information among those required by LRF and the LAI. Thus, it was concluded that the Mato Grosso municipalities studied, are not adequately disclosing the information required by the Fiscal Responsibility Act and the Access to Information Act.
Keywords: Lei de Responsabilidade Fiscal; Lei de acesso a informação; Evidenciação de informações; Transparência na gestão pública; Fiscal responsibility act; Access to information act; Information disclosure; Transparency in public management; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis